2016
DOI: 10.1097/iae.0000000000000913
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Safety Profile of Intravitreal Ziv-Aflibercept

Abstract: Single intravitreal injections of ziv-aflibercept into eyes with neovascular age-related macular degeneration appear to be safe through 1 month. Ziv-aflibercept could become a safe, low-cost therapy for macular diseases in developing countries and in those where intravitreal aflibercept (Eylea) is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 20 publications
1
53
1
2
Order By: Relevance
“…The compounded ziv-aflibercept drug was stable for 4 weeks as shown indirectly by good clinical response in the current study and directly by VEGF assays showing no loss of VEGF blockade at 1-month storage 12. The current study was carried out using polycarbonate barrel syringes that have poor binding to protein and excellent safety profile 12…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The compounded ziv-aflibercept drug was stable for 4 weeks as shown indirectly by good clinical response in the current study and directly by VEGF assays showing no loss of VEGF blockade at 1-month storage 12. The current study was carried out using polycarbonate barrel syringes that have poor binding to protein and excellent safety profile 12…”
Section: Discussionmentioning
confidence: 73%
“…Several case reports and small case series dealing with age-related macular degeneration or central retinal vein occlusion8–13 experienced visual gains without change in the electroretinogram recordings. Electroretinogram analysis in 12 subjects with wet age-related macular degeneration revealed no alterations 1 month after a single intravitreal ziv-aflibercept injection 12. The only mention of the use of ziv-aflibercept in DME comes from one phase I study:9 two patients with DME were treated in one eye and examined 1 week postinjection: the first had a decrease in CMT of 64 μm from 508 to 443 μm with visual improvement from 20/800 to 20/100; the second had a decrease in CMT of 352 μm from 720 to 368 μm with visual improvement from 20/800 to 20/200 at 1 week.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Short-term safety of intravitreal ziv-aflibercept has been reported in small case series, 7,8 and 1-month electroretinographic studies detected no postinjection abnormalities. 9 Flattening of neovascular PEDs with anti-VEGF therapy would seem to be a desirable morphologic effect, but the long-term advantages of this outcome remain unclear. Neither Chan 1 nor Khanani (subset analysis of HARBOR trial, ARVO 2015, E-abstract 5363) found a visual acuity benefit when 2.0-mg ranibizumab significantly decreased PED height compared with that achieved with 0.5-mg ranibizumab.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference in osmolarity between aflibercept and ziv-aflibercept may impair retinal function, and so the off-label use of zivaflibercept in RVO needs further assessment. It has been reported that off-label use of ziv-aflibercept improves VA without ocular toxicity and may offer a cheaper alternative to aflibercept, [43,44] in the same way that bevacizumab is cheaper than ranibizumab. Ziv-aflibercept is supplied at 25 mg/ml in single-use vials of 100 mg in 4 ml or 200 mg in 8 ml of 0.1% polysorbate 20, 100 mM sodium chloride, 5 mM sodium citrate, 5 mM sodium phosphate, and 20% sucrose in water for injection USP, pH 6.2.…”
Section: The Zaltrap Phase I/ii Trial Nct02173873mentioning
confidence: 99%